Physiognomic responses of páramo tussock grass to time since fire in northern Ecuador - Gutiérrez-Salazar, Patricia (2020)
Ecologically-sound management plans for high-altitude grasslands of the Andes depend on an understanding the responses of plants to fire, especially the dominant tussock grasses. This study considers physiognomic responses of tussock grass in 13 sites in northern Ecuador with a known fire history, with time since fire 0.5–10 y, and a control site which had not been burned for at least 40 y. At each site, we assessed vegetation height, basal cover of the tussocks, and the ratio of dead:live leaves in tussocks. We also measured light at ground level. As recovery time increased, tussock cover and number decreased, while tussock height increased. Light levels fell sharply below the tussock canopies as recovery took place, and dead leaves accumulated quickly, reaching 60 – 70% by just two years after fire. The modification of physical tussock structure is likely to influence a much wider ecosystem response to fire, and determines directly the fuel load for future fires. Despite these clear changes in tussock characteristics, they were too variable to be used as a reliable bioindicator of time since fire. However, a better understanding of the responses of tussock grasses to fire and particularly its impact on other species should become the focus of further attention in future.